Experimental study of the impedance behavior of 18650 lithium-ion battery cells under deforming mechanical abuse. (December 2019) - Spielbauer, Markus; Berg, Philipp; Ringat, Michael; Bohlen, Oliver; Jossen, Andreas
Highlights: Stepwise abuse tests on 18650 lithium-ion batteries with various impactor geometries and states of charge are executed. Simultaneous measurements of voltage, force, temperature and electrochemical impedance are performed. Damage mechanisms are assessed by computed tomography. Internal short circuits lead to the decrease of ohmic resistance for frequencies above 100 Hz, while measurements of lower frequencies indicate deviations from stationarity or linearity requirements. Compression of the cylindric jelly roll causes an increase in ohmic resistance. Abstract: Due to rising safety requirements for lithium-ion batteries, the detection of mechanical failure of such batteries is becoming increasingly important. As publications investigating electrochemical impedance spectroscopy (EIS) of lithium-ion battery cells under deforming mechanical abuse as a potential damage detection method are sparse, this work presents tests with stepwise loading of 18, 650 lithium-ion battery cells with various impactors (nails, cylindric, hemispheric) and simultaneous EIS measurements to search for indicators which could be used to anticipate hazardous events. The occurrence of different damage mechanisms of the jelly roll is evaluated via computed tomography (µ-CT) and correlated to the measured changes in EIS. For internal short circuits (ISCs) without instantaneous thermal runaway, the results show a decrease of ohmic resistance in the EIS for high measurement frequencies, which is possibly linked to temperature increase, while low frequencies indicate deviations from stationarity or linearity requirements. In the case of large area compression, the EIS measurements display an increase of ohmic resistance, which may be connected to various mechanisms, such as the decrease of porosity of the separator and the active materials or delamination.